Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

What is the solution to the system of equations below?
2x + 3y = 6
x - 3y = 9
-1.
(A)
(B) (-3,-4)
5,
(C)
8,
3
3
(D)


Sagot :

Answer:

x = 5

y = -4/3

Step-by-step explanation:

2x + 3y = 6

x - 3y = 9

Substitution Method:

x = 3y + 9

2(3y+9) + 3y = 6

6y + 18 + 3y = 6

9y = -12

y = -12/9 or -4/3

x - 3(-4/3) = 9

x + 4 = 9

x = 5